Multivariate prediction of long COVID headache in adolescents using gray matter structural MRI features - Kim, Minhoe; Sim, Sunkyung; Yang, Jaeseok; Kim, Minchul (Frontiers in Human Neuroscience, 2023)
Objective Headache is among the most frequent symptoms after coronavirus disease 2019 (COVID‑19), so-called long COVID syndrome. Although distinct brain changes have been reported in patients with long COVID, such reported brain changes have not been used for predictions and interpretations in a multivariate manner. In this study, we applied machine learning to assess whether individual adolescents with long COVID can be accurately distinguished from those with primary headaches. Methods Twenty-three adolescents with long COVID headaches with the persistence of headache for at least three months and 23 age- and sex-matched adolescents with primary headaches (migraine, new daily persistent headache, and tension-type headache) were enrolled. Multivoxel pattern analysis (MVPA) was applied for disorder-specific predictions of headache etiology based on individual brain structural MRI. In addition, connectome-based predictive modeling (CPM) was also performed using a structural covariance network. Results MVPA correctly classified long COVID patients from primary headache patients, with an area under the curve of 0.73 (accuracy = 63.4 %; permutation p = 0.001). The discriminating GM patterns exhibited lower classification weights for long COVID in the orbitofrontal and medial temporal lobes. The CPM using the structural covariance network achieved an area under the curve of 0.81 (accuracy = 69.5 %; permutation p = 0.005). The edges that classified long COVID patients from primary headache were mainly comprising thalamic connections. Conclusions The results suggest the potential value of structural MRI-based features for classifying long COVID headaches from primary headaches. The identified features suggest that the distinct gray matter changes in the orbitofrontal and medial temporal lobes occurring after COVID, as well as altered thalamic connectivity, are predictive of headache etiology.